CURRENT TREND IN NAMING BABIES IN JAVANESE COMMUNITY - Prabandari, Carla Sih (International Journal of Humanity Studies (IJHS), 2017)
The process of naming newborn babies is inseparable from the culture where they belong. Among Javanese people, there is a change of trends in naming babies. As western, noble, and religion associated names, such as Amelia, Gupita, Arsyad, gain popularity, modest and old-fashioned names, such as Tugino and Pariyem disappear. This paper Â discusses the trend in the naming of babies in Javanese community at the present time. Three theories are employed in the analysis. I will apply Saussurean Semiology and Bathesian Semiology and try to relate them to Stuart Hall's Theory of Identity. As a name is just an element of cultural identities, changing trends in naming in Javanese culture does not entirely change their identity as Javanese people.DOI: https://doi.org/10.24071/ijhs.2017.010107